Nonylphenol reduced the number of haploids in in vitro spermatogenesis of the endangered cyprinid Gnathopogon caerulescens. (June 2023) - Nishie, Tomomi; Komaru, Aika; Shiroguchi, Syota; Yamaizumi, Takako; Ono, Yuriko; Motomochi, Atsuko; Tooyama, Ikuo; Fujioka, Yasuhiro; Sakai, Noriyoshi; Higaki, Shogo; Takada, Tatsuyuki
Abstract: Nonylphenol (NP), an endocrine disrupting chemical, is widely used in industrial and agricultural processes, causing NP influx into aquatic environments. NP induces hormonal imbalance, and male feminization, and reduces germ cell production during spermatogenesis; however, the mechanism by which it affects spermatogenesis remains unknown. Here, we investigated the effect of NP on spermatogenesis in honmoroko ( Gnathopogon caerulescens), an endangered fish endemic to Lake Biwa, Japan, using an in vitro differentiation system. We collected spermatogonia from the testes of non-spawning G. caerulescens and subjected them to suspension culture. The spermatogonia differentiated into flagellated spermatozoa in 3 weeks, regardless of the presence of NP. NP concentrations as low as 1 nM caused a decrease in the number of germ cells in a dose-dependent manner, whereas the number of somatic cells decreased only at a high concentration of 1 μM. Flow cytometric analysis revealed that the decrease in germ cell number was attributed to haploids (spermatids and spermatozoa); the number of spermatogonia and spermatocytes was not affected by NP treatment. This result is consistent with the hypothesis that NP might repress the second meiosis or induce apoptosis in haploids. This study demonstrated that the combination of in vitro germ cell differentiation and flow cytometric analysis is useful for evaluating the direct effects of NP on germ cell differentiation in endangered endemic fish. Highlights: Nonylphenol reduces the number of haploid cells during spermatogenesis. In vitro spermatogenesis reduces the experimental duration. Nonylphenol affects spermatogenesis even at low concentrations (1 nM). Nonylphenol may repress the second meiosis or induce apoptosis in haploid cells. In vitro spermatogenesis and flow cytometry enables quantitative evaluation of chemicals.